On the Brody hyperbolicity of the complex space $\mathbb C^3$ avoiding complex and real hyperplanes - Jalled, Abdessami (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We study the Brody hyperbolicity of а complex space $\mathbb C^3$ avoiding the arrangement of complex and real hyperplanes in $\mathbb C^3$. We also investigate the projection onto the projective complex space $\mathbb C P^2$ of holomorphic maps $f\colon \mathbb C→\mathbb C^3$ avoiding this configuration.